Síntese e caracterização de novos compostos de difenilfosfinatos de chumbo(II) e mercúrio(I) e (II) - Schwade, Vânia Denise (2009)
In this work, nine new compounds of lead(II) and mercury(I) and (II)diphenylphosphinates were synthesized, among them four are lead(II) compounds with diphenylphosphinates, hydroxo and water ligands, obtained in reactions using diphenylphosphinic acid, lead(II) oxide and lead(II) acetate in methanol, ethanol and water solvents. There are: [{Pb3(μ3 OH)(μ O2PPh2)3}(μ3 O2PPh2)3Pb(O2PPh2)]·2,25CH3OH·0,5H2O, 1, [{Pb3(μ3 OH)(μ O2PPh2)3}(μ3 O2PPh2)3Pb(μ O2PPh2)2 {Pb(OH2)}(μ O2PPh2)]n·0,62CH3OH·0,38H2O, 2, [Pb4(μ3 OH)4(μ O2PPh2)4]·2CH3OH, 3, and [{Pb3(μ3 OH)(μ O2PPh2)3}(μ3 O2PPh2)3Pb(μ3 O2PPh2)3{Pb3(μ3 OH)(μ O2PPh2)3}]·2CH3CH2OH·2CH3OH, 4. The compounds 1, 2 and 4 were obtained from the filtered solution from the reactions and were structurally characterized by single-crystal X-ray diffraction, revealing molecular (1 and 4) and polymeric strucutres (2). Five diphenylphosphinates compounds containing bpe or 4,4 -bipy ligands were synthesized from the initial compound of [Pb(O2PPh2)2]n or [Hg(O2PPh2)2]n, which are: [{Pb(μ O2PPh2)2}(μ bpe){Pb(μ O2PPh2)2}]n, 5, [Hg(O2PPh2)2(bpe)]n·2H2O, 6, [{{Hg2(O2PPh2)}2 (μ O2PPh2)2}(μ bpe)2]n·(CH3)2SO·3H2O, 7, [Hg(O2PPh2)2(4,4-bipy)]n·H2O, 8, and [{Hg(O2PPh2)}(μ O2PPh2)2{Hg(μ O2PPh2)(μ bipy)}2(μ O2PPh2)2{Hg(O2PPh2)(μ bipy)}]n ·2CH3OH·3H2O, 9. The compounds 5, 7, 9 were characterized with single-crystal X-ray diffraction, revealing unidimensional polymeric (5 and 7) and bidimensional (9) compounds. The compound 7 is a compound where the Hg(II) metal center was reduced in the presence of the methanol redutor agent in mixture with dimethylsulfoxide, in high temperature of the reaction. The compound 9 was formed from the filtered solution of the synthesis reaction from compound 8. In the polynuclear lead(II) compounds exists 4, 5 and 3½ crystallography independent lead atoms (in the asymmetric unit) for compounds 1, 2 and 4, respectively. Compound 1 has one methanol molecule with strong interaction with one of the lead atoms of the structure, and compound 2 has one water coordinated molecule to one lead atom from the asymmetric unit. The compound 4, with 7 lead atoms in the total, has one of them localized in center of symmetry, and that has half occupation factor. In compound 7 there is one Hg2 2+ ion in the asymmetric unit, and in compound 9, two mercury(II) atoms. The coordination polymer growth is given by translation operation in one determined crystallographic direction. In 2, the growth is given in the [0 1 0] direction by the diphenylphosphinates ligands; in 5, in the [1 0 0] direction by diphenylphosphinates ligands; in 7, in the [1 1¯ 0] direction by the bpe ligands; and in 9, in the (0 1 0) plane by the 4,4 -bipy ligands. In the crystal structures, the diphenylphosphinates ligands presents four main coordination modes: bridge between three lead(II) atoms (compounds 1, 2 and 4), bridge between two lead(II) atoms (compounds 1, 2, 4 and 5) or mercury(I) or mercury(II) (compounds 7 and 9), terminal form (1, 7 and 9), and yet in bridge and chelate mode (in 9). Other different coordination mode occurs in the compound 2, where two ligands make bridge between two lead atoms and interact with one third lead atom, allowing the polymeric arrangement. The hydroxo ligand coordinates to three lead(II)atoms in the compounds 1, 2 and 4. The infrared spectroscopic analysis were held to the all obtained compounds, and the thermogravimetric and powder X-ray diffraction analysis were performed only in the cases in which the sample quantity was sufficient for this.